MEMBUMIKAN KONSEP SYARIAH DALAM EKONOMI BERBASIS KERAKYATAN (BAITUL MAAL WAT TAMWIL SEBAGAISEBUAH SOLUSI) - Mafruhah, Izza (Universitas Muhammdaiyah Surakarta, 2002)
Economic crisis happened in Indonesian in 1997 gave enormous impacts. One of the serious impacts struck in banking. The people who are accustomed serious shock because of the bank liquidation. At that time, the appearance of banks with syariah principles, which at first did not get serious attention, started to take into consideration as safe banks. The profit sharing concept started to show the establishment and existence of Indonesian Muamalat Bank in Indonesian crisis situation.To save small-scale economic people, which also underwent the impact of monetary crisis, ICMI (Indonesian Moslem Scholarship Association), MUI (Indonesian Ulama Council) and BMI (Indonesian Muamalat Bank) encourage Indonesian Muamalat Bank, which established in 1994.BMT (Baitul Maal Wat Tamwil) is one of the Islamic Banking commitment for economic system based on the democracy. There are a lot of obstacles and hindrance faced by Syariah Banking including BMT. However all the obstacles and hindrance can be solved with discipline and professionalism to achieve the goal of